The Fertility of Theories - Segall, Robert (Department of Philosophy, 2014)
In addition to empirical adequacy and compatibility with other current theories, scientific theories are commonly judged on three criteria ' simplicity, elegance, and fertility. Fertility has received comparatively little attention in the philosophical literature. A definition of a certain sort of fertility, called P-fertility, proposed by Ernan McMullin, is that it consists in the capacity of a theory to be successfully modified over time to explain new experimental data or theoretical insights. McMullin made the major claim that he has a novel and perhaps the sole argument for Scientific Realism. His argument involves two strands (i) theories must be considered diachronically and it is an historical fact that long standing successful scientific theories are P-fertile, and (ii) the correct explanation of this fact is that these theories reflect the realities of a mind-independent world. A rebuttal of McMullin's position given in the literature is considered and rejected. His argument therefore requires further consideration. The plausible first strand of McMullin's argument is accepted for the purposes of discussion, and thus the observation requires explanation, either along McMullin's own lines or otherwise. The concept of diachronicity and the implications of accepting a diachronic view of scientific theories are considered. The identity of theory across time can be understood both from a Realist and an Anti-realist perspective via the concept of significant claims in the successive versions of the long standing successful theories. This defuses a possible objection to McMullin's argument, namely that by assuming diachronicity he begs the question against the Anti-realist. Explanations of the conjunction of success and P-fertility are examined from the perspective of Scientific Realism and the major current Anti-realist stances ' Entity Realism, Structural Realism, Instrumentalism, and Internal Realism. 3 To justify the second strand of McMullin's argument, a notion of the approximate truth or of the verisimilitude of theories is required. Inter alia it is argued that a distinction must be made between the approximate truth of a scientific theory and that of a simple assertion or a simple narrative. The concepts of the approximate truth of scientific theories and their verisimilitude are explored and some serious difficulties are identified. First, it is difficult to accommodate differences in respect as well as in degree in delineating the nature of an approximately true theory. Second, it is difficult to give a satisfactory account of the metric used to assess the verisimilitude of theories. It is argued that in any case no version of these concepts can adequately support the second strand of McMullin's thesis. This is because, at best, approximate truth and verisimilitude can only support a pragmatic claim ' the improved empirical adequacy of successive versions of the long standing theory. In contrast, McMullin's thesis requires that successor versions generally are better theories. Third, there is an intractable theory dependent weighting problem posed by the open ended nature of scientific theories in contrast with the closed narratives describing idealized models. The role of the approximate truth of scientific theories is explored, within the frameworks of Realism and Anti-realism, with regard to the possible responses to the existence of two highly successful, well corroborated, but incompatible theories ' general relativity and quantum mechanics. It is suggested that Scientific Realism itself, not only McMullin's argument for Scientific Realism, requires the notion of approximate truth or verisimilitude of theories. Putnam's Internal Realism is considered, and, if as I suggest, no adequate account of the concepts of the approximate truth or verisimilitude of scientific theories can be given, Internal Realism (which need not draw on these concepts because of its denial that there is a unique correct description of the world) is more plausible than the full blooded Scientific Realism advocated by McMullin, despite granting the claim of the historical observation of the conjunction between long standing successful theories and their P-fertility.